Efficacy of Cold Plasma for Direct Deposition of Antibiotics as a Novel Approach for Localized Delivery and Retention of Effect - Los, Agata; Ziuzina, Dana; Boehm, Daniela; Han, Lu; O'Sullivan, Denis; O'Neill, Liam; Bourke, Paula (Frontiers in Cellular and Infection Microbiology, 2019)
Antimicrobial coating of medical devices has emerged as a potentially effective tool to prevent or ameliorate device-related infections. We investigated a novel plasma deposition process for direct deposition of pharmaceutical drugs on to a range of surfaces and assessed retention of structure function relationship and antimicrobial efficacy against mono-species biofilms. Two selected sample antibiotics – ampicillin and gentamicin, were deposited onto two types of surfaces – polystyrene microtiter plates and stainless steel coupons. The antimicrobial efficacy of the antibiotic-coated surfaces was tested against challenge populations of both planktonic and sessile E. coli and P. aeruginosa, with responses monitored for up to 14 days. The plasma deposition process bonded the antibiotic to the surfaces, with localized retention of antibiotic activity. The antibiotics deposited on the test surfaces retained a good efficacy against planktonic cells, and importantly prevented biofilm formation of attached cells for up to 96 hours. The antibiotic rapidly eluted from the surface of antibiotic-coated surfaces to the surrounding medium, with retention of effect in this surrounding milieu for up to 2 weeks. Control experiments established that there was no independent antimicrobial or growth promoting effect of the plasma deposition process, where there was no antibiotic in the helium plasma assisted delivery stream. Apart from the flexibility offered through deposition on material surfaces, there was no additive or destructive effect associated with the helium assisted plasma deposition process on the antibiotic. The plasma assisted process was a viable means of coating clinically relevant materials and developing innovative functional materials with retention of antibiotic activity, without employing a linker or plasma modified polymer, thus minimizing bio-compatibility issues for medical device materials. This offers potential to prevent or control instrumented or non-permanent device associated infection localized to the surgical or implant site.